The concept of daily life in occupational therapy: culture, subjectivity and the social and historical context - Galheigo, Sandra Maria (Revista de Terapia Ocupacional da Universidade de São Paulo, 2003)
This article discusses the use of the concept of daily life in Occupational Therapy. It presents a bibliographic review of the use of the concept in Social Science, Social Psychology and Philosophy. After that it argues that the inovation in the use of the concept is associated with changes in theoretical and methodological assumptions since the critical perspective seeks to address the relationship between Subject and History. It opposes the positivist model, which aims at the training of activities of daily living, to the critical perspective, which seeks to attribute critical meaning to the daily life of the subject.